Using Chain Massage Game to Support Young Learners’ VAK Learning Style - Yella Dezas Perdani (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2021)
The research examined the use of a chain massage game to accommodate the visual, auditory, and kinesthetic learning style of the young learners. It discovered how the teacher prepared and implemented the chain massage games, and how it accommodated and profited the visual, auditory, and kinesthetic students learning style. This research was a qualitative study and used observation and interview as the data collection techniques. The result showed that the teacher prepared and applied the chain massage game very well, could control all the students, and did all the steps she planned in applying the game in the class, and the students learned English excitedly. Furthermore, it was revealed that there were four advantages of using chain massage game. The first advantage is that playing the game fosters interaction between the teacher and students, as well as between students and their classmates. Second, instruction becomes more student-centered. Third, engaging students in the teaching-learning process through the chain message game is successful, especially at the elementary level. The fourth advantage is that the chain massage game enables students to practice new vocabulary.